El cas únic de no menys 'encara que, malgrat això' en el Curial e Güelfa i un altre italianisme no observat. - MARTÍNEZ-MARTÍNEZ, CATERINA (Scripta)
Curial and Guelfa reveals itself to us as quite a philological challenge when it comes to characterizing Catalan, which is rich in multilingualism and multiculturalism; and, even more so, if, considering the repercussion of this language model for contemporary Catalan, we examine the filigree of constructions with which it is woven. In this work, we look at the first and only documentation in Catalan of no menys with the concessive value of 'even though, in spite of '. To do this, we turn to the historical lexicography of the environmental languages of Naples at the time (French and Italian) and to the literary sources (authors and texts, works, clichés and literary figures) from which the work. Thus, we will try to discern if, indeed, it is another Italianism, in this case, not observed until now. Alive in the author's linguistic model, it seems that no menys was grafted onto an example of the Catalan of the Curial and Guelfa in the form of «language transfer».